1999
DOI: 10.1094/cchem.1999.76.5.589
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Hull‐less Barley

Abstract: Cereal Chem. 76(5):589-599Hull-less barley (HB) has been investigated in many countries for use in feed, food, and industry since the publication of the last review in 1986. Literature published since 1990 on various aspects of HB utilization, other than in monogastric feeds, has been reviewed. Several HB cultivars containing low or high β-glucan, low or high extract viscosity, and waxy (0-5% amylose) or normal starch are now available. Interest in HB utilization in the food industry developed largely due to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
165
2
12

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(200 citation statements)
references
References 80 publications
(119 reference statements)
21
165
2
12
Order By: Relevance
“…However, the naked barley showed a high degree of variation of total protein for the seven investigated cultivars and the two growing regions of between 125 and 225 g kg -1 (Tables 1, 2, 3). These values and high variation in the protein content of naked barley are supported by the literature [9], but the cause for the variations between the different cultivars is still unclear.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…However, the naked barley showed a high degree of variation of total protein for the seven investigated cultivars and the two growing regions of between 125 and 225 g kg -1 (Tables 1, 2, 3). These values and high variation in the protein content of naked barley are supported by the literature [9], but the cause for the variations between the different cultivars is still unclear.…”
Section: Resultsmentioning
confidence: 54%
“…The total protein content has been documented for naked barley as being between 12 and 16% of dry mass [9]. The influence of Fusarium infection on grain protein composition has been mainly investigated on wheat cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…The 50%, 60% and 70% barley cookies had pronounced baked-barley aroma and flavour, and were dry and grainy in texture. The graininess of cookies with barley flour might be because of the higher distribution of larger flour particle size of the high β-glucan barley flour (40.7% in the 250-425 μm) versus smaller particle size of AP flour (>90% under 150 μm) (Bhatty 1999). This might suggest that 30% substitution is more appropriate than 50% for the level of barley flour.…”
Section: Resultsmentioning
confidence: 99%
“…Enzymes, orge nue, digestibilité, performances de croissance, porcs A number of previous studies have shown that hulless barley contains a reduced concentration of fibrous constituents and a higher concentration of nutrients, such as protein, than hulled barley, indicating a superiority of hulless barley over hulled barley for swine (Mitchell et al 1976;Bhatty 1986;Baidoo and Liu 1998). However, the performance of pigs or poultry fed diets based on hulless barley is not consistently superior to that of animals fed hulled barley (Aherne and Spicer 1986;Thacker et al 1988 …”
Section: Mots Clésmentioning
confidence: 99%